PENILAIAN WILLINGNESS TO PAY PERBAIKAN KUALITAS UDARA MENGGUNAKAN CONTINGENT VALUATION METHOD - Rosalina, Rosalina; Gravitiani, Evi (Jurnal Ekonomi & Studi Pembangunan, 2014)
Abstract: The economic growth in the urban areas is characterized by the growth of the industrial sector and traffic density. The increase in the amount of factories and motorized vehicles caused an increase in gas emission in the air. Residual smoke from factory production processes and gas emission are stationary and mobile sources of pollution, which interfere with the air quality in the urban areas. These effects human health negatively. This research was calculating the willingness to pay (WTP) with the contingent valuation method. This research aims to determine the public awareness to keep their environment clean. It is indicated by people’s WTP on policy implication that offered once every year. The strategy offered to diminish the stationary sources of pollution is reforestation. While the strategies offered to diminish the mobile sources of pollution are: 1) improvement in transportation infrastructure; 2) reforestation; 3) replacement of old motorized vehicles; and 4) the use of alternative roads on traffic peak hours. The strategies to diminish the mobile sources of pollution were ranked by an Analytical Hierarchy Process (AHP) according to people’s preference in the implementation. The strategies have implications in four consecutive years. The research result showed that the level of WTP of the society was still low. The determinant factors of the WTP are estimated by the ordered probit method. The estimated results showed that the income of the respondents compared to health costs, caused by damaged lungs, eyes, and nose, has an influence on the WTP. While the age, education, and distance to the polluted area of the respondents are not significantly influencing the WTP. Abstrak: Pembangunan ekonomi di perkotaan ditandai dengan perkembangan di sektor industri dan diikuti oleh aktivitas transportasi yang padat. Peningkatan jumlah pabrik dan kendaraan bermotor menghasilkan gas buang di udara yang semakin meningkat. Asap sisa proses industrialisasi dan gas buang kendaraan bermotor (emisi) menjadi polusi sumber tidak bergerak dan sumber bergerak yang mengganggu kualitas udara di perkotaan dan berdampak buruk terhadap kesehatan. Studi ini menghitung kesediaan masyarakat membayar (WTP) terhadap kebijakan memperbaiki kualitas udara dengan tujuan mengetahui kesadaran masyarakat menjaga lingkungannya. Kesediaan membayar masyarakat ditunjukkan dengan seberapa besar masyarakat mau membayar kebijakan yang ditawarkan tiap setahun sekali. Kebijakan yang ditawarkan untuk polusi sumber tidak bergerak adalah penghijauan sedangkan untuk polusi sumber bergerak ada empat kebijakan. Empat kebijakan untuk polusi sumber tidak bergerak diranking dengan analisis AHP dengan urutan perbaikan infrastruktur, penghijauan, penggantian kendaraan bermesin tua, dan pengalihan jalur padat. Hasil menunjukkan bahwa tingkat WTP masyarakat masih rendah. Faktor-faktor yang mempengaruhi WTP masyarakat adalah pendapatan dan biaya kesehatan paru-paru, mata, dah hidung. Faktor usia, tingkat pendidikan, dan jarak polusi terhadap responden tidak begitu berpengaruh.